Теплопостачання в Україні: сучасний стан та перспективи розвитку - Ширяєва, Наталя Володимирівна; Білоцерківський, Олександр Борисович; Братков, М. О. (НТУ "ХПІ", 2014)
У статті розглянуто питання теплопостачання в Україні. Досліджено проблеми теплопостачання у житловому фонді країни. Розглянуто тарифи на теплову енергію, проаналізовано особливості їх формування та динаміку за 2007–2015 роки залежно від виду сезону. Досліджено питання видобутку паливно-енергетичних ресурсів в Україні, надано рекомендації щодо їх економного використанням населенням у побуті. Зроблено висновок про незначне підвищення тарифів на теплову енергію для населення та пропозиції щодо використання надлишків газу та вугілля.

The question of heating in Ukraine is considered in the paper. The problems of heating in the country’s available housing are investigated. Due to the age of the biggest part of the housing, it is very difficult to keep warm inside by a wick system pressure. In cities, many Ukrainian apartment blocks are linked to «district heating» networks. In theory, this is a highly efficient system, using the heat that would normally be wasted from power stations to warm water that is then pumped into buildings. But country’s heating program provides the tariffs changing. Heat energy tariffs are presented for 2007-2015. The features of their forming and dynamics are analyzed. It was concluded that the seasonality make a big affect on tariffs. The production problem of energy resources in Ukraine is studied. Recommendations for their economical use of public life are provided. A conclusion of a slight increase in tariffs for the heat energy to the population and suggestions for the use of excess gas and coal are made.
The Heating Supply in Ukraine: current state and development prospects
Keywords: теплозаощадження; паливно-енергетичні ресурси; теплоенергетика; енергозалежність; heat saving resources; combined heat and power